2020
DOI: 10.1001/jamanetworkopen.2020.28477
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Posttraumatic Stress Disorder and Educational Achievement in Sweden

Abstract: This population-based cohort study investigates the association between posttraumatic stress disorder and objective indicators of educational attainment across the life span, controlling for familial factors shared by full siblings, psychiatric comorbidity, and general cognitive ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…28 Regarding the relationship between PTSD and AP, some studies showed that students with higher self-reported PTSD symptoms were prone to having lower GPAs, 29 students with lower AP had a higher prevalence of PTSD, 30 and PTSD was associated with lower odds of achieving each of the educational milestones during the study period. 31 Nevertheless, results from other studies found that the direct correlation between PTSD and AP was not significant. 4,26 This difference can be attributed to the heterogeneity among studies, such as different study populations and social backgrounds.…”
Section: Introductionmentioning
confidence: 90%
“…28 Regarding the relationship between PTSD and AP, some studies showed that students with higher self-reported PTSD symptoms were prone to having lower GPAs, 29 students with lower AP had a higher prevalence of PTSD, 30 and PTSD was associated with lower odds of achieving each of the educational milestones during the study period. 31 Nevertheless, results from other studies found that the direct correlation between PTSD and AP was not significant. 4,26 This difference can be attributed to the heterogeneity among studies, such as different study populations and social backgrounds.…”
Section: Introductionmentioning
confidence: 90%
“…Its manifestations include intrusive memories, flashbacks and dreams of the event, avoidance of trauma-related cues, as well as mood, dissociative, sleep and cognitive symptoms [ 8 ]. People suffering from PTSD experience disability, occupational and educational problems, poorer social support and relational difficulties [ 9 , 10 , 11 ]. Typically, PTSD has an acute onset up to 6 months after the traumatic experience, and a chronic course is frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous mental health problems may lower resilience in the face of MSI or other trauma as well as increase the risk of poor PTSI outcomes. Previous mental health issues may also be associated with lower education attainment, 28 worse general health, 29 and worse social functioning. 30 , 31 Previous research has highlighted that a diagnosis of posttraumatic stress disorder is associated with reduced educational performance across the lifespan, 28 but to our knowledge, ours is the first study to identify lower educational background as a risk factor for developing PTSI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mental health issues may also be associated with lower education attainment, 28 worse general health, 29 and worse social functioning. 30 , 31 Previous research has highlighted that a diagnosis of posttraumatic stress disorder is associated with reduced educational performance across the lifespan, 28 but to our knowledge, ours is the first study to identify lower educational background as a risk factor for developing PTSI. To examine these issues in more depth, well-designed prospective studies are needed to follow cohorts of workers experiencing workplace injuries and accidents, ideally with biopsychosocial characteristics of the workers and workplaces measured before the injury event occurs.…”
Section: Discussionmentioning
confidence: 99%